(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The main difference between active and passive solar heating is that active heating uses sunlight in the form of heat or electricity to enhance heating systems. Whereas passive heating takes heat from the sun as it enters your home through windows, roofs and walls to heat items in your home.